Molecularly imprinted polymer-specific solid-phase extraction for the determination of 4-hydroxy-2(3H)benzoxazolone isolated from Acanthus ilicifolius Linnaeus using high-performance liquid chromatography-tandem mass spectrometry - Ma, Xingbin; Lin, Hongling; Yong, Yanhong; Ju, Xianghong; Li, Youquan; Liu, Xiaoxi; Yu, Zhichao; Wujin, Cuomu; She, Yongxin; Zhang, Jiyu; Abd El-Aty, A. M. (Frontiers in Nutrition, 2022)
A major constituent found in Acanthus ilicifolius Linnaeus, 4-hydroxy-2 (3H) benzoxazolone alkaloid (HBOA), has a range of versatile applications. Herein, a quick and straightforward method for extracting HBOA from Acanthus ilicifolius Linnaeus was proposed. HBOA was used as a template, whereas 4-vinylpyridine, ethylene glycol dimethacrylate, and acetonitrile were used as a functional monomer, cross-linker, and porogen, respectively. Molecularly imprinted polymers (MIPs) were synthesized by precipitation polymerization, and their adsorption isotherms, dynamics, and selective binding ability were characterized and analyzed. The results showed that the adsorption amount of the template was 90.18 mg/g. The MIPs were used as solid-phase extraction fillers and actual sample extraction columns, with a linear range of 0.1–10 mg/g, average recovery of 84.61%–105.8%, and a relative standard deviation of 1.50%–2.27%. The HBOA concentrations in the roots, stems, and leaves were 1226, 557, and 205 μg/g, respectively. In addition, MIP–SPE was successfully used in isolating and purifying HBOA from different parts of Acanthus ilicifolius Linnaeus, indicating its effectiveness in extracting and determining HBOA in other herbs.